Overview of the Arctic Sea State and Boundary Layer Physics Program. Issue 12 (11th December 2018) - Thomson, Jim; Ackley, Stephen; Girard‐Ardhuin, Fanny; Ardhuin, Fabrice; Babanin, Alex; Boutin, Guillaume; Brozena, John; Cheng, Sukun; Collins, Clarence; Doble, Martin; Fairall, Chris; Guest, Peter; et al.
Abstract: A large collaborative program has studied the coupled air‐ice‐ocean‐wave processes occurring in the Arctic during the autumn ice advance. The program included a field campaign in the western Arctic during the autumn of 2015, with in situ data collection and both aerial and satellite remote sensing. Many of the analyses have focused on using and improving forecast models. Summarizing and synthesizing the results from a series of separate papers, the overall view is of an Arctic shifting to a more seasonal system. The dramatic increase in open water extent and duration in the autumn means that large surface waves and significant surface heat fluxes are now common. When refreezing finally does occur, it is a highly variable process in space and time. Wind and wave events drive episodic advances and retreats of the ice edge, with associated variations in sea ice formation types (e.g., pancakes, nilas). This variability becomes imprinted on the winter ice cover, which in turn affects the melt season the following year. Key Points: A large study of air‐ice‐ocean‐waves interactions was completed during the autumn of 2015 in the western Arctic Strong wave‐ice feedbacks, including pancake ice formation and wave attenuation, were observed Autumn refreezing of the seasonal ice cover is controlled by ocean preconditioning, atmospheric forcing (i.e., on‐ice versus off‐ice winds), and mixing events